A Comparative Study on Low and High Salinity Tolerance of Two Strains of Pinctada fucata - Sun, Jing; Chen, Mingqiang; Fu, Zhengyi; Yang, Jingru; Zhou, Shengjie; Yu, Gang; Zhou, Wenli; Ma, Zhenhua (Frontiers in Marine Science, 2021)
This study compares salinity tolerance between red and black shell Pinctada fucata salinity stress of 20 and 50‰, while 35‰ was used as a control. The hemolymph osmotic pressure, inorganic ion concentration, the activities of Na+-K+ -ATPase, respiratory metabolism related enzymes and liver tissue antioxidant related enzymes were measured at 12 and 24 h after salinity stress. The osmotic pressure and inorganic ion concentration of hemolymph of two strains P. fucata increased significantly with the increase of salinity. The activity of Na+-K+ -ATPase of red P. fucata only decreased under low salinity at 24 h, and was significantly higher than that the control under low salinity at 12 h and high salinity at 12 and 24 h. The succinate dehydrogenase (SDH) activities of the P. fucata treatment groups were significantly higher than those the control at 12 h. The lactate dehydrogenase (LDH) activity increased significantly with salinity at 12 h. and the black P. fucata LDH activity was significantly higher than the control at 24 h, while the LDH activity of red P. fucata was significantly lower than that the control in 50‰ salinity. The superoxide dismutase (SOD) activity of black P. fucata was significantly lower than that the control, while that of red P. fucata was significantly higher than that the control within 24. At 12 h, the catalase (CAT) activity of red P. fucata increased significantly with salinity, but decreased significantly with salinity at 24 h. The CAT activity of black P. fucata was highest at 24 h under low salinity. Glutathione peroxidase (GSH-Px) and alkaline phosphatase (AKP) activities of red P. fucata were significantly higher than those the control under low or high salinity. At high salinity for 24 h, the GSH-Px activity was lowest in black P. fucata, AKP activity was highest. The present study indicates that the physical responses of P. fucata to the salinity stress vary with shell colors. The red P. fucata can quickly respond positively to the change of environmental salinity and reduce the damage caused by the change of environmental salinity.